Frankenstein, or, The modern Prometheus - Shelley, Mary
For centuries, the story of Victor Frankenstein and the monster he created has held readers spellbound. On the surface, it is a novel of tense and steadily mounting dread. On a more profound level, it illuminates the triumph and tragedy of the human condition in its portrayal of a scientist who oversteps the bounds of conscience, and of a creature tortured by the solitude of a world in which he does not belong. A novel of almost hallucinatory intensity, Mary Shelley's Frankenstein represents one of the most striking flowerings of the Romantic imagination